Rheumatic Mitral and Aortic Valve Disease- A Case Report from USA - Roychoudhury, Debasish; Nanda, Navin C; Hon, John J; Filsoufi, Farzan; Salma, Ahmed Y; Akdogan, Raziye E (Cardiovascular Journal, 2018)
Although virtually eradicated in the United States, rheumatic heart disease still carries a sinister outcome causing significant mortality and morbidity in developing countries in Asia, Africa and the Pacific Islands where it still remains in endemic form. Our case involves a 35-year-old female patient born and raised in India who recently migrated to the United States. Her echocardiogram revealed severe combined aortic and mitral valve stenosis and severe aortic regurgitation. We hereby analyze echocardiographic findings in concomitant rheumatic aortic and mitral valve disease with preserved left ventricular (LV) systolic function. We also discuss treatment implications with combined surgical replacements of both valves with mechanical prostheses. Cardiovasc. j. 2018; 11(1): 81-85